2022
DOI: 10.2147/rmhp.s354377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus on the Immunity of Tuberculosis Patients: A Retrospective, Cross-Sectional Study

Abstract: Background Tuberculosis (TB) is an infectious disease that poses a significant health threat and is one of the leading causes of death worldwide. Diabetes mellitus (DM) has high morbidity and mortality rates. Previous studies have reported that comorbidities can influence one another and aggravate immune disorders. A systematic and comprehensive evaluation of the immune status of patients with TB and DM (TB-DM) is helpful for early clinical immune intervention and for promoting the recovery of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
1
21
0
5
Order By: Relevance
“…However, TNF- α , as mentioned above, was increased in the OP group, which is probably due to the secretion of TNF- α by other immune cells. Immune cells in the body will differentiate and produce different types of cytokines under the influence of various factors and mediate infectious or noninfectious diseases [ 37 ]. We will further explore the reasons for the increase in TNF- α in the senile OP population in future mechanistic studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, TNF- α , as mentioned above, was increased in the OP group, which is probably due to the secretion of TNF- α by other immune cells. Immune cells in the body will differentiate and produce different types of cytokines under the influence of various factors and mediate infectious or noninfectious diseases [ 37 ]. We will further explore the reasons for the increase in TNF- α in the senile OP population in future mechanistic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Before initialing TPT, identifying LTBI accurately was one of the challenges faced as current available LTBI diagnostic tools were based on the immune response. Previous studies have found that poor glycemic control may lead to a blunted immune response ( 12 , 13 ). Neutrophil chemotaxis and oxidative killing potential were reduced in DM patients compared to nondiabetic controls, and leukocyte bactericidal activity was reduced, especially in patients with poor glycemic control ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It indicated participants with C-TST conversion in the baseline IGRA-negative group are more inclined to the true LTBI status. T2DM patients may have a false-negative TST or C-TST due to immunosuppression ( 12 , 33 ). However, the use of the booster effect to increase the detection of LTBI had been recommended in different populations, including immunosuppressed patients as well as healthy population ( 34 – 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-y level is negatively correlated with HbA1c glycated hemoglobin levels. Poorly treated diabetes also increases the severity of tuberculosis [24,25].…”
Section: Tuberculosis Risk Factors Over the Centuriesmentioning
confidence: 99%